A fine line : how design strategies are shaping the future of business. - Esslinger, Hartmut, ....- (San Francisco : Jossey-Bass, 2009)
Foreword. The Author. Introduction. Chapter 1: Design-Driven Strategy: Staking a Claim in the Creative Economy. Chapter 2: True Lies: The Role of Leadership in Innovation. Chapter 3: Designing to Win: The Creative Business Strategy. Chapter 4: Minds Beat Money: The Innovation Process, Step by Step. Chapter 5: A Business Design Revolution: The Greening of Planet, Inc. Chapter 6: Design-Driven Strategies for Better Business-And a Better World. Chapter 7: The Factories. Epilogue. Resources.